SOFTWARE FOR AUTOMATION OF STATE ECOLOGICAL PROJECT EXPERTISE - V. A. Rybak; M. A. Gatih; S. I. Obraztsov; V. V. Valenteychik (Наука и техника)
A new information technology for automation of state ecological project expertise  has been developed in the process of research. The technology is intended for specialists of Ministry of Natural Resources and Environmental Protection of the Republic of Belarus. The paper contains description of the gridding to the GIS electronic maps of situation plans concerning location of facilities used for economic activities and diagrams of environment contamination sources, information technology for an analysis of calculation results in respect of dispersion of pollutant emissions, functions pertaining to reflection of  calculation results on electronic topographic map.